Demonstration of a Broadband Photodetector Based on a Two‐Dimensional Metal–Organic Framework. Issue 9 (23rd January 2020) - Arora, Himani; Dong, Renhao; Venanzi, Tommaso; Zscharschuch, Jens; Schneider, Harald; Helm, Manfred; Feng, Xinliang; Cánovas, Enrique; Erbe, Artur
Abstract: Metal–organic frameworks (MOFs) are emerging as an appealing class of highly tailorable electrically conducting materials with potential applications in optoelectronics. Yet, the realization of their proof‐of‐concept devices remains a daunting challenge, attributed to their poor electrical properties. Following recent work on a semiconducting Fe3 (THT)2 (NH4 )3 (THT: 2, 3, 6, 7, 10, 11‐triphenylenehexathiol) 2D MOF with record‐high mobility and band‐like charge transport, here, an Fe3 (THT)2 (NH4 )3 MOF‐based photodetector operating in photoconductive mode capable of detecting a broad wavelength range from UV to NIR (400–1575 nm) is demonstrated. The narrow IR bandgap of the active layer (≈0.45 eV) constrains the performance of the photodetector at room temperature by band‐to‐band thermal excitation of charge carriers. At 77 K, the device performance is significantly improved; two orders of magnitude higher voltage responsivity, lower noise equivalent power, and higher specific detectivity of 7 × 10 8 cm Hz 1/2 W −1 are achieved under 785 nm excitation. These figures of merit are retained over the analyzed spectral region (400–1575 nm) and are commensurate to those obtained with the first demonstrations of graphene‐ and black‐phosphorus‐based photodetectors. This work demonstrates the feasibility of integrating conjugated MOFs as an active element into broadband photodetectors, thus bridging the gap between materials' synthesis and technological applications. Abstract : 2D metal–organic framework (MOF) films of Fe3 (THT)2 (NH4 )3 are employed as an active element in a two‐terminal photodetector device, operating in the UV‐to‐NIR region. Owing to the small bandgap of the MOF samples (≈0.45 eV), the photodetectors are best operated at 77 K. This is attributed to the suppression of thermally activated charge carriers at low temperatures, leading to improved performance of the device.